2007
DOI: 10.1128/cvi.00285-06
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Antibodies Directed to Paracoccidioides brasiliensis Glycosphingolipids during the Course of Paracoccidioidomycosis Treatment

Abstract: Paracoccidioidomycosis (PCM) is a granulomatous disease caused by the dimorphic fungus Paracoccidioides brasiliensis. The immunoglobulin classes and isotypes of antibodies directed to acidic glycosphingolipids (GSLs) and glucosylceramide of P. brasiliensis were determined by enzyme-linked immunosorbent assay of sera from 31 PCM patients. The reactivities of 38 serum samples were analyzed by considering the stage of treatment: before antifungal treatment (n ‫؍‬ 10), during 1 to 4 months of treatment (T1-4; n ‫؍… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 28 publications
0
23
0
3
Order By: Relevance
“…In dimorphic fungi, such as Histoplasma capsulatum, Paracoccidioides brasiliensis and Blastomyces dermatiditis, the production of GlcCer is mainly related to the yeast-pathogenic form, leading to the presence of antibodies to GlcCer in patient sera and suggesting its importance for fungal virulence [63,65,66]. In the plant pathogen Penicillium digitatum, knocking out the GlcCer synthase gene impairs its virulence in a citrus fruit infection model [67], suggesting that GlcCer plays an important role in virulence not only of mammal pathogens but also of plant pathogens.…”
Section: Sphingolipids As Targets For Treatment Of Fungal Infections mentioning
confidence: 99%
“…In dimorphic fungi, such as Histoplasma capsulatum, Paracoccidioides brasiliensis and Blastomyces dermatiditis, the production of GlcCer is mainly related to the yeast-pathogenic form, leading to the presence of antibodies to GlcCer in patient sera and suggesting its importance for fungal virulence [63,65,66]. In the plant pathogen Penicillium digitatum, knocking out the GlcCer synthase gene impairs its virulence in a citrus fruit infection model [67], suggesting that GlcCer plays an important role in virulence not only of mammal pathogens but also of plant pathogens.…”
Section: Sphingolipids As Targets For Treatment Of Fungal Infections mentioning
confidence: 99%
“…Patients undergoing treatment for paracoccidioidomycosis showed first an IgM response and then IgG1, and some even had IgA and IgE production (8). Only 1 of 6 patients with invasive candidiasis and 2 of 14 patients with aspergillosis were found to have antibodies to glycosylinositolphosphorylceramide antigens (8). Although the role of these antibodies during infection is still under investigation, their presence supports the idea of an immunomodulatory role for GSLs.…”
Section: Fungal Gslmentioning
confidence: 91%
“…These human antibodies were able to inhibit C. neoformans growth and budding (77). A recent publication showed antibodies to acidic complex GSLs during paracoccidioidomycosis (8). Patients undergoing treatment for paracoccidioidomycosis showed first an IgM response and then IgG1, and some even had IgA and IgE production (8).…”
Section: Fungal Gslmentioning
confidence: 99%
See 1 more Smart Citation
“…The second part of our study determined the levels of total IgG and its subclasses in chronic PCM patients before, during and after treatment. Some groups have attempted to determine a correlation between antibody levels and disease severity in PCM patients, especially in the follow-up period after treatment (Bueno et al 1997, Martins et al 1997, Reis et al 2005, Anastácio et al 2007, Bertini et al 2007, Yoshida et al 2009), but this association is still controversial. Restrepo et al (1978) found decreased antibody levels after six months of treatment using DI and CF tests in only three of the 16 patients analysed.…”
Section: Discussionmentioning
confidence: 99%